Producing subharmonics on violin by means of three elements: Twisted strings, bow location and rosin amount / Tayebeh Kiumarsi - Tayebeh , Kiumarsi (2015)
During the previous fifty years the world of classical music has been experiencing a timbral revolution, as well as violin and its techniques. A huge number of new and stimulating sounds and timbres have been discovered with the help of new extended techniques. To produce undertones lower than the fundamental frequency on a string instrument seems unexpected until a Japanese violinist Mari Kimura has reached the technique of playing low-pitched tones below the fundamental frequency. “A violin can reach the range of a cello” says Kimura. She has introduced this technique to the world as a musical element to extend the violin techniques in 1994 and called this phenomenon “Subharmonic”. Prior to Kimura in 1989 a music professor Fredrick Halgedahl and a scientist Roger Hanson had analyzed these tones then later Roger Hanson and Oliver Rodgers considered and introduced them as “Anomalous Low Frequency” or “ALF”, however Kimura has improved these anomalous low frequencies as musical terms in her articles and compositions. To produce subharmonic, the bow parameters like bow pressure, accurate bow placement and bow speed are mentioned as the most important and impressive elements. The main purpose of this research is to examine the elements and parameters which are used to produce subharmonics on the violin such as bow pressure, bow placement, twisting the string counterclockwise and the amount of rosin on the bow hair, although there are other affective factors to obtain subharmincs like bow speed, the age and thickness of the string. In this study in addition to other studies which has been done only on “G” string, the “D” string will be examined, too. In this empirical study, three violinists have tried to produce subharmonics on violin using three elements (bow placement, twisting the string and amount of rosin), and their performing have been recorded by a 4K digital camera recorder. The recordings will be used for comparative data analysis. In this study the results show that different bow placements, various dosages of rosin amount used on the bow hair and different numbers of twisted string cause different subharmonics on both G and D strings. The produced subharmonic intervals on G and D strings included diminished and perfect fifth, minor and major sixth, minor and major seventh, octave and minor and major ninth.